Self-perceived coping resources of middle-aged and older adults: results of a large population-based study - Böhlen, Friederike; Herzog, Wolfgang; Schellberg, Dieter; Maatouk, Imad; Saum, Kai-Uwe; Brenner, Hermann; Wild, Beate (Aging & mental health, 2017)
Objectives: Psychosocial resources (personal resources, social resources, and other) are important for coping with aging and impairment. The aim of this study was to describe the resources of older adults and to compare subgroups with frailty, complex health care needs, and/or mental disorders.Method: At the third follow-up of the large population-based German ESTHER study, 3124 elderly persons (aged 55-85) were included. Psychosocial resources were assessed during a home visit by trained study doctors by using a list of 26 different items. Resources were described for the total group, separated by sex, and for the three subgroups of persons with frailty, complex health care needs, and mental disorders.Results: Family, self-efficacy, and financial security were the most frequently reported resources of older adults. Women and men showed significant differences in their self-perceived resources. Personal resources (self-efficacy, optimism, mastery), social resources, and financial security were reported significantly less frequently by frail persons, persons with complex health care needs, and mentally ill older adults compared to non-impaired participants. Apart from external support, patients who experienced complex health care needs reported resources less frequently compared to frail and mentally ill patients.Conclusion: Coping resources in older adults are associated with sex and impairment. Evaluation and support of personal resources of frail or mentally ill persons or individuals with complex health care needs should be integrated in the therapeutic process.
Gesehen am 18.10.2017
Article was published online on 29 Aug 2016